1980
DOI: 10.1002/ar.1091960108
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest and placodal contributions in the development of the glossopharyngeal‐vagal complex in the chick

Abstract: By using the method of quail-to-chick transplantation of neural crest in one series (VNG) and placodal ectoderm in a second series (VPG) we were able to determine the relative contribution of cranial neural crest and placodal ectoderm to the formation of the Glossopharyngeal-vagal complex. In chimeric embryos, quail cells originating from cranial neural crest grafts of postotic levels end up in the root ganglia, while quail cells originating from placodal ectoderm of postotic levels end up in the trunk ganglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(52 citation statements)
references
References 17 publications
2
50
0
Order By: Relevance
“…41 for review). Such discrepancies may reflect the different embryological origins and different functions of these classes of neurons (45,46) and suggest that signaling in these two systems can be pharmacologically dissociated. Based on the sparse distribution of CARTp-ir DRG cell bodies described here, it seems likely that the dense plexuses of CARTp-ir fibers in the dorsal horn and trigeminal tract observed by ourselves and others (4) receive contributions also from CART-expressing populations other than primary afferent neurons.…”
Section: Discussionmentioning
confidence: 99%
“…41 for review). Such discrepancies may reflect the different embryological origins and different functions of these classes of neurons (45,46) and suggest that signaling in these two systems can be pharmacologically dissociated. Based on the sparse distribution of CARTp-ir DRG cell bodies described here, it seems likely that the dense plexuses of CARTp-ir fibers in the dorsal horn and trigeminal tract observed by ourselves and others (4) receive contributions also from CART-expressing populations other than primary afferent neurons.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the inferior ganglia of the cranial nerves V, VII, IX, and X (the nodose ganglion), are formed from two sources of cells; the epibranchial (ectodermal) placode, which contributes the neurons, and the neural crest, which produces supporting cells (Narayanan and Narayanan, 1980;D'Amico-Martel and Noden, 1983;reviewed by Le Douarin et al, 1984). Also, according to D'Amico-Martel and Noden (1983), the nodose placode releases neuroblasts to the ganglion primordium during stages 19 and 20 in the chick em- Lateral view of the stage 19 (4 days) chick embryo stained with EIC8 which specifically recognizes neurons and the circumpharyngeal crest, a subpopulation of the vagal crest cells.…”
Section: Nodose Placode and Neural Crest Cellsmentioning
confidence: 99%
“…(glossopharyngeal) and 10 th (vagus) cranial nerves as is the case in the chick (Hamburger, 1961;Noden, 1975: Narayanan & Narayanan, 1980and Le Douarin, 1982.…”
Section: Discussionmentioning
confidence: 95%
“…14), These sites are occupied by the proximal ganglionic primordia of the 9 ,h (glossopharyngeal), and 10 M (vagus) cranial nerves among other vertebrates (Noden, 1975(Noden, & 1978Narayanan & Narayanan, 1980), suggesting that the neural crest cells mesectoderm, may contribute to the formation of the proximal ganglia of these crania] nerves.…”
Section: Ragaa ML El-balshy Ei Almentioning
confidence: 99%